Peluang dan Tantangan Pembelajaran di Masa Pandemi Melalui Pemanfaatan Aplikasi Google Meet di Desa Sibrama Kecamatan Kemranjen - Fian, Khafifatul; Utami, Hastin Tri (Jurnal Kependidikan, 2022)
Education is a process of activities to transfer knowledge from educators to students. Until now, education is carried out online, so there is a need for application programs to support learning programs, one of which is the Google Meet application. The google meet application is one of the learning support application programs that can be done audio-visually. This study aims to provide information related to learning opportunities and challenges during the pandemic through the google meet application. This research is a field research with qualitative research methods and based on a phenomenological approach. The phenomenological approach is an approach that is based on the experience of human life. The research subjects are high school students, especially in Sibrama Village. The data were obtained through interviews conducted through google forms which contained questions related to the phenomena that the authors studied. Apart from this, the author also obtains data from documents or previous research related to what the author is researching. The author analyzes, describes, and summarizes some of the data obtained. The data analysis method used is qualitative data analysis with descriptive-analytical techniques. The results of the study show that special students in Sibrama Village still rarely use the google meet application by educators for learning, while the application that is often used is the WhatsApp Group application.